URANYL ADSORPTION AND SURFACE SPECIATION AT THE IMOGOLITE-WATER INTERFACE: SELF-CONSISTENT SPECTROSCOPIC AND SURFACE COMPLEXATION MODELS - Arai Y.; McBeath M.; Joye J.; Davis J.A.; Bargar J.R. (My University, 2006)
Macro- and molecular-scale knowledge of uranyl (U(VI)) partitioning reactions with soil/sediment mineral components is important in predicting U(VI) transport processes in the vadose zone and aquifers. In this study, U(VI) reactivity and surface speciation on a poorly crystalline aluminosilicate mineral, synthetic imogolite, were investigated using batch adsorption experiments, X-ray absorption spectroscopy (XAS), and surface complexation modeling. U(VI) uptake on imogolite surfaces was greatest at pH ~7-8 (I = 0.1 M NaNO3 solution, suspension density = 0.4 g/L [U(VI)]i = 0.01-30 μM, equilibration with air). Uranyl uptake decreased with increasing sodium nitrate concentration in the range from 0.02 to 0.5 M. XAS analyses show that two U(VI) inner-sphere (bidentate mononuclear coordination on outer-wall aluminol groups) and one outer-sphere surface species are present on the imogolite surface, and the distribution of the surface species is pH dependent. At pH 8.8, bis-carbonato inner-sphere and tris-carbonato outer-sphere surface species are present. At pH 7, bis- and non-carbonato inner-sphere surface species co-exist, and the fraction of bis-carbonato species increases slightly with increasing I (0.1-0.5 M). At pH 5.3, U(VI) non-carbonato bidentate mononuclear surface species predominate (69%). A triple layer surface complexation model was developed with surface species that are consistent with the XAS analyses and macroscopic adsorption data. The proton stoichiometry of surface reactions was determined from both the pH dependence of U(VI) adsorption data in pH regions of surface species predominance and from bond-valence calculations. The bis-carbonato species required a distribution of surface charge between the surface and β charge planes in order to be consistent with both the spectroscopic and macroscopic adsorption data. This research indicates that U(VI)-carbonato ternary species on poorly crystalline aluminosilicate mineral surfaces may be important in controlling U(VI) mobility in low-temperature geochemical environments over a wide pH range (~5-9), even at the partial pressure of carbon dioxide of ambient air (pCO2 = 10-3.45 atm). © 2006 Elsevier Inc. All rights reserved.